Hyaluronan receptors as mediators and modulators of the tumor microenvironmen - Carvalho, Ana M. (2022)
The tumor microenvironment (TME) is a dynamic and complex matter shaped by heterogenous cancer and cancer-associated cells present at the tumor site. Hyaluronan (HA) is a major TME component that plays pro-tumorigenic and carcinogenic functions. These functions are mediated by different hyaladherins expressed by cancer and tumor-associated cells triggering downstream signaling pathways that determine cell fate and contribute to TME progression towards a carcinogenic state. Here, we review the interaction of HA with several cell-surface hyaladherins â CD44, RHAMM, TLR2 and 4, LYVE-1, HARE and layilin. We discuss the signaling pathways activated by these interactions and the respective response of different cell populations within the TME, and the modulation of the TME. Potential cancer therapies via targeting these interactions are also briefly discussed.